Videolaryngoscopy versus direct laryngoscopy for adults undergoing tracheal intubation: a Cochrane systematic review and meta-analysis update. (October 2022) - Hansel, Jan; Rogers, Andrew M.; Lewis, Sharon R.; Cook, Tim M.; Smith, Andrew F.
Abstract: Background: Tracheal intubation is a commonly performed procedure that can be associated with complications and result in patient harm. Videolaryngoscopy (VL) may decrease this risk as compared with Macintosh direct laryngoscopy (DL). This review evaluates the risk and benefit profile of VL compared with DL in adults. Methods: We searched MEDLINE, Embase, CENTRAL, and Web of Science on February 27, 2021. We included RCTs comparing VL with DL in patients undergoing tracheal intubation in any setting. We separately compared outcomes according to VL design: Macintosh-style, hyperangulated, and channelled. Results: A total of 222 RCTs (with 26 149 participants) were included. Most studies had unclear risk of bias in at least one domain, and all were at high risk of performance and detection bias. We found that videolaryngoscopes of any design likely reduce rates of failed intubation (Macintosh-style: risk ratio [RR]=0.41; 95% confidence interval [CI], 0.26–0.65; hyperangulated: RR=0.51; 95% CI, 0.34–0.76; channelled: RR=0.43, 95% CI, 0.30–0.61; moderate-certainty evidence) with increased rates of successful intubation on first attempt and better glottic views across patient groups and settings. Hyperangulated designs are likely favourable in terms of reducing the rate of oesophageal intubation, and result in improved rates of successful intubation in individuals presenting with difficult airway features ( P =0.03). We also present other patient-oriented outcomes. Conclusions: In this systematic review and meta-analysis of trials of adults undergoing tracheal intubation, VL was associated with fewer failed attempts and complications such as hypoxaemia, whereas glottic views were improved. Systematic review registration: This article is based on a Cochrane Review published in the Cochrane Database of Systematic Reviews (CDSR) 2022, Issue 4, DOI: 10.1002/14651858.CD011136.pub3 (see www.cochranelibrary.com for information ). Cochrane Reviews are regularly updated as new evidence emerges and in response to feedback, and the CDSR should be consulted for the most recent version of the review.